2019
DOI: 10.4142/jvs.2019.20.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiation and leukoreduction on down-regulation of CXCL-8 and storage lesion in stored canine whole blood

Abstract: White blood cells (WBCs) and storage period are the main factors of transfusion reactions. In the present study, cytokine/chemokine concentrations after leukoreduction (LR) and irradiation (IR) in stored canine whole blood were measured. Red blood cell storage lesion caused by IR and LR were also compared. Blood samples from 10 healthy Beagles were divided into four groups (no treatment, LR-, IR-, and LR + IR-treated). Leukocytes were removed by filtration in the LR group and gamma radiation (25 Gy) was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“… 40–42 Compared with the study by Corsi and others, 40 the CXCL8 concentrations in the lyophilised platelets were similar to non-leukoreduced red blood cell units stored for ≥28 days, while the TNFα concentrations were 10-fold lower than in non-leukoreduced units and threefold lower than in leukoreduced units. Compared with the study by Yang and others, 42 the CXCL8 concentrations in the lyophilised platelets are lower than in red blood cell units stored for ≥14 days, while all TNFα concentrations were below the assay’s detectable range. In all non-leukoreduced units in the Purcell study, 41 the CXCL8 concentrations were greater than in the lyophilised platelet units in the present study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“… 40–42 Compared with the study by Corsi and others, 40 the CXCL8 concentrations in the lyophilised platelets were similar to non-leukoreduced red blood cell units stored for ≥28 days, while the TNFα concentrations were 10-fold lower than in non-leukoreduced units and threefold lower than in leukoreduced units. Compared with the study by Yang and others, 42 the CXCL8 concentrations in the lyophilised platelets are lower than in red blood cell units stored for ≥14 days, while all TNFα concentrations were below the assay’s detectable range. In all non-leukoreduced units in the Purcell study, 41 the CXCL8 concentrations were greater than in the lyophilised platelet units in the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…Comparisons with stored red blood cell units might enable assessment of the potential clinical relevance of the cytokine concentrations measured in the lyophilised platelet units. Several groups have assessed the cytokine concentrations of stored canine red blood cells, with and without leukoreduction 40–42. Compared with the study by Corsi and others,40 the CXCL8 concentrations in the lyophilised platelets were similar to non‐leukoreduced red blood cell units stored for ≥28 days, while the TNFα concentrations were 10‐fold lower than in non‐leukoreduced units and threefold lower than in leukoreduced units.…”
Section: Discussionmentioning
confidence: 97%
“…In our survey, the IL‐8 median concentration remained at low levels in LR WB and LR pRBC units, during all the storage period, while an increasing trend was observed in nLR units. Similarly, previous studies found that leukoreduction prevented IL‐8 accumulation in canine pRBC, while it significantly increased in nLR units during storage 36,39,40 . Even though IL‐8 has no direct pyrogenic effects, it has been speculated that the passive inoculation of cytokines might have a synergistic effect on the cytokine network of critically ill patients, contributing to the systemic inflammatory response 41 .…”
Section: Discussionmentioning
confidence: 76%
“…In a previous study, IL-6 concentration was higher in canine WB than in LR or irradiated WB at every storage time, but it did not increase in a time-dependent manner, while TNFα was under the detection limit in all the groups. 36 A significant increase in aPTT values and a simultaneous decrease in fibrinogen, factors VII, VIII, and IX concentration were observed in WB between T0 and T35. No significant differences were observed between WB at T0 and FFP, as well as between WB at T35 and FFP, demonstrating that, contrary to a common belief, the WB maintains good levels of clotting factors during all the storage period, including those considered more labile factors.…”
Section: Discussionmentioning
confidence: 93%
“…M. haemocanis was not considered because its existence has been unclear in Korea. In-house leukoreduced-packed RBC from the donor was prepared using a closed collection and filter system (Blood Bag with RBC Filter and Safety DDA Plus 3 Quadruple 400 ml; Tae-Chang Industrial, Daegu, Korea) [4]. The mPCV of the recipient dog was 36% after the blood transfusion.…”
Section: Case Descriptionmentioning
confidence: 99%